2020
DOI: 10.1111/ppc.12546
|View full text |Cite
|
Sign up to set email alerts
|

The effects of health belief model‐based education and acupressure for coping with premenstrual syndrome on premenstrual symptoms and quality of life: A randomized‐controlled trial

Abstract: This study investigated the effects of health belief model-based education and acupressure for coping with premenstrual syndrome (PMS) on premenstrual symptoms and quality of life. Design and Methods: The sample size was identified as 163 women. While the acupressure education group-administered education and acupressure, the education group-administered only education. No intervention made to the control group. Findings: There was a significant difference between the pretest and posttest total mean scores of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…Similarly, several studies have shown that educational approaches can manage PMS symptoms. [17][18][19] In this regard, Taylor et al 30 conducted a study to determine the effectiveness of peer group education on PMS in women. Consistent with this study, they showed that education by peers significantly reduces the PMS score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, several studies have shown that educational approaches can manage PMS symptoms. [17][18][19] In this regard, Taylor et al 30 conducted a study to determine the effectiveness of peer group education on PMS in women. Consistent with this study, they showed that education by peers significantly reduces the PMS score.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, researchers emphasize choosing educational approaches as the first step in managing adolescent PMS. [17][18][19] Evidence shows that peer group is one of the effective ways to educate adolescents to improve health-related behaviors. The purpose of peer education is to develop knowledge, attitudes, and proper health behaviors by those who are not professionally trained but have common experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 199 Psychoeducation alone has been shown to be effective in reducing symptoms of PMS in two randomized control trials. 194 , 200 …”
Section: Treatment Reviewmentioning
confidence: 99%
“…The form that was prepared by the researchers by reviewing the relevant literature (6,12,16) consisted of 28 questions inquiring about the participants' sociodemographic characteristics, as well as their menstrual characteristics.…”
Section: Identifying Information Formmentioning
confidence: 99%